Diagnosis, management and long term cardiovascular outcomes of phenotypic profiles in pulmonary hypertension associated with congenital diaphragmatic hernia - Chaudhari, Tejasvi; Schmidt Sotomayor, Nadia; Maheshwari, Rajesh (Frontiers in Pediatrics, 2024)
Congenital diaphragmatic hernia (CDH) is a developmental defect of the diaphragm resulting in herniation of viscera into the chest. This condition is characterized by pulmonary hypoplasia, pulmonary hypertension (PH) and cardiac ventricular dysfunction. PH is a key component of the pathophysiology of CDH in neonates and contributes to morbidity and mortality. Traditionally, PH associated with CDH (CDH-PH) is thought to be secondary to increased pulmonary arterial resistance and vasoreactivity resulting from pulmonary hypoplasia. HoweverAdditionally, there is increasing recognition of associated left ventricular hypoplasia, dysfunction and elevated end diastolic pressure resulting in pulmonary venous hypertension in infants with CDH. Thus, hemodynamic management of these infants is complex and cautious use of pulmonary vasodilators such as inhaled nitric oxide (iNO) is warranted. We aim to provide an overview of different phenotypic profiles of CDH associated PH and potential management options based on current evidence and pathophysiology.